STUDI DRAINASE BERWAWASAN LINGKUNGAN UNTUK JALAN PANGERAN ANTASARI BANJARMASIN - Holdani Kurdi; Akhmad Zairin (INFO-TEKNIK, 2013)
Pangeran Antasari road which located in Eastern District of Banjarmasin frequent damage to roads due to drainage channels do not function properly , resulting in a puddle of water on the road . Therefore drainage planning is a good way on the road , in order to determine the design rainfall and discharge large plan dimensions of effective drainage on the road .This anaysis use rainfall data and calculate the maximum that would be obtained by Log Pearson III methods . It is examined in conformance testing , after that recalculated rainfall to rainfall intensity obtained by the method Mononobe . The area of the drainage channel is calculated per section and see the conditions in the field can then be used to calculate water discharge plan using rational methods that will be used to plan the dimensions of good drainage and economical as well as applying the concept ekodrainase.In the cross-sectional results of drainage planning on Prince Street Antasari water discharge plan obtained ranged from 0.7317 to 1.631 m2/sec for left and right channels on Pangeran Antasari road planned Square -shaped channel . with 3 ( three ) comparisons : ( 1 ) precast concrete channel with reference steel ( N = 0,011 ) with the cross-sectional area ranged from 0.5802 to 0.7296 m2 right channel and left channel 0.5033 to 0.7836 m2 . ( 2 ) soil Channel created by Excavator ( N = 0028 ) with cross-sectional area ranged from 0.8237 to 1.0803 m2 right channel and left channel 0.7145 to 1.1124 m2 . ( 3 ) Channel masonry ( N = 0.03 ) with the right- channel cross-sectional area ranged from 0.8453 to 1.1086 and from 0.7332 to 1.1416 m2 left channel .